PENGEMBANGAN MODUL MATA KULIAH PRAKTIK LAS DAN TEMPA LANJUT DI PROGRAM STUDI PENDIDIKAN TEKNIK MESIN FKIP UNIVERSITAS SEBELAS MARET SURAKARTA - Rahman Sidik Pamungkas; Suharno Suharno; Husin Bugis (Fakultas Keguruan dan Ilmu Pendidikan Universitas Sebelas Maret Surakarta, 2019)
The purpose of this research is to increase the independence and effectiveness in learning, to develop learning modules in the course welding practice and further metal handiwork in Mechanical Engineering Education Program of Teacher Traning and Education Science Faculty of Sebelas Maret University Surakarta. This research is Research and Development. The research has conducted with several stages, starting from the potential and problems, data collection, product design, design validation, design revisions, the initial product, product revision and final product. Subjects were expert assessment of the product, namely instructional media lecturer, welding practice and further metal handiwork lecturer, and students. The type of data used is qualitative data. Data collection techniques using instruments in the form of sheets of interviews and questionnaires. Analysis of data using questionnaire analysis and feasibility analysis of advanced welding modules. Based on the research results, the feasibility of advanced welding module in the first phase of matter experts obtained 81.61% and from 77.78% obtained by media experts, with the criteria very well. Assessment on the second phase of matter experts gained 87.5% and 88.194% earned media expert with the criteria very well. Questionnaire responses percentage of students obtained an average score of 83.27% with the criteria very well. Thus, advanced welding module on manufacture of swing educational materials viable for use in learning.